Barriers of adopting environmental management practices in the micro and small island chalets operation - Jamaludin, Mariam; Yusof, Zeenat Begam (e-international Publishing House Ltd, 2016)
Sustainability becomes main management issues for hospitality firms. Big hospitality firms conduct countless attempts to accommodate into the sustainability agenda. However, the small hospitality firms are left behind. The reason is some barriers that are dragging them. Barriers studies regarding big hospitality companies are plenteous. However, studies regarding barriers of MSIC operators are limited in Malaysia. Therefore, the objectives are to identify the barriers and the ranking of the barriers. This study is applying the quantitative and qualitative approach. The finding shows that lack of green products is the most salient barrier. In conclusion, this study has managed to identify barriers and provide some recommendations.